Genome size shifts: karyotype evolution in Crepis section Neglectoides (Asteraceae). (9th April 2015) - Enke, N.; Kunze, R.; Pustahija, F.; Glöckner, G.; Zimmermann, J.; Oberländer, J.; Kamari, G.; Siljak‐Yakovlev, S.; Keurentjes, J.
Abstract Plant genome size evolution is a very dynamic process: the ancestral genome of angiosperms was initially most likely small, which led to a tendency towards genome increase during evolution. However, findings in several angiosperm lineages demonstrate mechanisms that also led to genome size contraction. Recent molecular investigations on the Asteraceae genus Crepis suggest that several genomic reduction events have occurred during the evolution of the genus. This study focuses on the Mediterranean Crepis sect. Neglectoides, which includes three species with some of the smallest genomes within the whole genus. Crepis neglecta has the largest genome in sect. Neglectoides, approximately twice the size of the two species Crepis cretica and Crepis hellenica. Whereas C. cretica and C. hellencia are more closely related to each other than to C. neglecta the karyotypes of the latter species and C. cretica are similar, while that of C. hellenica differs considerably. Here, the karyotypic organisation of the three species is investigated with fluorescence in‐situ hybridisation and studied in a molecular phylogenetic framework based on the nuclear markers Actin, CHR12, CPN60B, GPCR1 and XTH23. Our findings further corroborate the occurrence of genome size contraction in Crepis, and suggest that the difference in genome size between C. neglecta and C. cretica is mostly due to elimination of dispersed repetitive elements, whereas chromosomal reorganisation was involved in the karyotype formation of C. hellenica.